Evolving Fuzzy Neural Network Based Load Prediction Model In Dynamic Cell Sizing - Angela, Amphawan (2003)
Cellular networks have gained importance in today's mobile communication scenario. The deployment of first and second-generation cellular systems has involved extensive planning, both to achieve continuous RF coverage and to ensure the provision of capacity in the right locations. The process has been a costly one, accounting for 50-70% of the total network cost. With the explosive growth in the number of cellular subscribers, operators are constantly striving to meet demand. Call blockage during the peak traffic hour is one of greatest concerns of operators. The traffic increase may be accommodated by either adding more carriers to existing cell-sites, or by splitting the cell into several amaller cells. Both methods require the operator to derive a new frequency plan. Additionally , if cell splitting is performed, a new coverage plan will be required to ensure intercell interference is kept to a minimum. The cost of installing new hardware (transceivers and base stations) and devising new frequency and coverage plans is considerable.